Soybean-Nodulating Rhizobia: Ecology, Characterization, Diversity, and Growth Promoting Functions - Nakei, Monica D.; Venkataramana, Pavithravani B.; Ndakidemi, Patrick A. (Frontiers in Sustainable Food Systems, 2022)
Soybean (Glycine max) is one of the most important legumes in the world. While inoculation with rhizobia has been shown to improve N2 fixation and subsequent yield of soybean. The efficiency of the symbiosis differs with the type of rhizobia species. Therefore, a complete understanding of the ecology of indigenous soybean-nodulating rhizobia concerning their genetic diversity and the environmental factors associated with their localization and dominance in the soil is important. This review aims to understand the potential of indigenous soybean-nodulating rhizobia through a synthesis of the literature their characterization, genetic diversity, symbiotic effectiveness, as well as their functions in Biological Nitrogen Fixation (BNF) and biocontrol of soybean soil-borne pathogens.